Secularization Theory and Its Interaction With Modernity - Orujova, Elnara (Scholarya Demo Journal of Ruby, 2021)
This article deals with the social changes brought about by secularization in the modern world. This topic is considered one of the current topics in sociology. The process of secularization whıch concerns with modernity has been central interest of classical sociologists. The purpose of this article is to examine the social changes brought about by secularization on the basis of facts, considering time and geographical regions. The article first explains the concepts of modernity, religion and secularization. According to the study, secularization, which is one of the features of modernity, has not led to conclusions occuring in the same direction. Various outcomes have been obtained at various times and in various areas. Sociologists’ views on whether secularization is an ideology or a theory have been observed. According to many who regard religion to be an ideology, intentional change is also a reason for the elimination or weakening of religion. Sociologists have come to different conclusions at different times when studying the role of religion in human life. First of all, they stressed the important role of religion in human life. Later, as a result of secularization, they came to the conclusion that religion would lose its significance or disappear. Today, however, most sociologists are of the opinion that this theory has not proved its worth, that religion has not only lost its essence, but that it still exists in a way that can keep pace with many differences.